Licensing Services in the Capital Investment Services and Integrated One Door Service (Dpmptsp) Banda Aceh City - Cut Putri Ellyana; Ismail Ismail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Integrated Service Officers and licensing carry out their work based on Standard Operating Procedures (SOP) that apply to meet community expectations. Desired expectations in the future for Licensing Services are related to adequate facilities, infrastructure / service facilities, customer knowledge or abilities, good technical skills, attitudes and behaviors of officers to realize one-stop service properly, it is necessary to maintain the service supervision function licensing both internally and externally. The purpose of the research is to describe the licensing service procedures at the Banda Aceh City investment and integrated services office (DPMPTSP) as well as analyze the function of supervision of licensing services at the Capital Investment and One Stop Integrated Services Office (DPMPTSP) of Banda Aceh City. In this case the researchers used various theories to analyze the results of various research findings using a qualitative approach. Researcher data collection is done by observation, interview and also document analysis. Researcher observation data obtained from the treatment, while other information researchers dug through interviews with informants. To convince researchers, also analyzed the documents that exist at the Banda Aceh City Investment and Integrated Services Office (DPMPTSP). The results showed the standard components of licensing services such as facilities, infrastructure / service facilities were still not optimal. Relating to the attitude and behavior of officers, showing openness in conducting services. Then the licensing service supervision function has not been running optimally because it has not been done directly and routinely by supervisors in controlling subordinates. Likewise, the oversight of the DPR and the public is also poor.